Interfacial cfDNA Enrichment and Amplification with On‐Chip Thermoplasmonics for Highly Sensitive Cancerous Liquid Biopsy - Danhua Wang; Linlin Liu; Wenjing Chi; Zhenping Liu; Jiayun Wu; Yirou Liang; Fei He; Ruixiang Zhang; Pengxin Huang; Yunbo Li; Guangyu Qiu (Advanced Science)
Abstract Tumor‐derived cell‐free DNA (cfDNA) has been exploited as an effective liquid biopsy biomarker for early cancer diagnosis. However, the fragmented and low‐abundance nature in circulating blood pose challenges for highly sensitive cfDNA quantification. Herein, a multifunctional plasmonic biosensor termed Interfacial cfDNA Enrichment, Amplification and Sensing with on‐chip Thermoplasmonics (INEAST) is developed for cfDNA‐based liquid biopsy and lung cancer diagnosis. The INEAST biosensor achieved in situ thermoregulation and label‐free cfDNA biosensing by simultaneously harnessing interfacial thermoplasmonics and localized surface plasmon resonance. Typical cfDNA biomarkers, including epidermal growth factor receptor (EGFR), tumor protein 53 (TP53), phosphatase and tensin homologue deleted on chromosome 10 (PTEN), and cyclin‐dependent kinase inhibitor (CDKN2A), are quantified with detection limits down to femtomolar‐level. Through further validation using blood samples from lung cancer patients, the proposed INEAST bioassays demonstrated superior reliability for lung cancer screening, particularly when combined with clinically available tumor‐protein metrics. This study demonstrated that the INEAST biosensor enables rapid and sensitive cfDNA quantification, yielding a promising and compatible liquid biopsy for early‐stage lung cancer diagnosis.